Unusual Stepwise Protonation and J‐Aggregation of meso‐Tetrakis(N‐methylpyridinium‐4‐yl)porphine on Binding Poly(sodium vinylsulfonate). Issue 36 (18th July 2013) - Castriciano, Maria Angela; Samperi, Mario; Camiolo, Salvatore; Romeo, Andrea; Monsù Scolaro, Luigi
Abstract The binding of a tetracationic porphyrin to a highly charged polymer like poly(sodium vinylsulfonate) has been investigated over a wide pH range and under various experimental conditions. We present evidence that, depending on the pH, the high electrostatic field exerted by the polymer stabilizes the diprotonated form of the free base porphyrin at unusual pH values or otherwise causes the formation of H‐type aggregates. In particular, at a low polymer concentration, lowering the pH at first allows the formation of the diacid species then it determines its reorganization in close‐packed J‐type aggregates. The employment of various metallo‐derivatives of the title porphyrin enables a better insight into the nature of all the detected species.